INTRODUCTION OF THE MY WEIGHT LOSS DIET APPLICATION AS AN INTERVENTION IN ADOLESCENT OBESITY MANAGEMENT - Ariestiningsih, Ayuningtyas Dian; Tritisari, Kanthi Permaningtyas; Wilujeng, Catur Saptaning; Cempak, Anggun Rindang; Kusumastuty, Inggita; Handayani, Dian (Caring: Jurnal Pengabdian Masyarakat, 2024)
Obesity has been an alarming global health issue that relates to nutrition intake. In Indonesia, the prevalence of obesity among individuals aged over 18 years showed upward trend from 2013 to 2018 as reported by the Basic Health Research. Obesity is a key factor contributing to the development of metabolic syndrome. Addressing this issue requires adequate education to the public on obesity prevention through various methods. This community service program was conducted in the form of webinars, held on July 4, 2021, and July 11, 2021 on Zoom and was attended by 424 participants. Several topics were discussed in the webinars, including deep dive into obesity, its management, dietary planning, and an introduction to the My Weight Loss Diet application. A notable improvement in participants understanding was evident as seen from increased post-test scores. My Weight Loss Diet application is expected to assist participants in regulating their food intake in order to prevent obesity.